Hidden Spaces of Empire: Italian Colonists in Nineteenth-Century Peru. Issue 1 (26th November 2021) - Riall, Lucy
Abstract: Among the clichés in modern European history, one of the most common is of Italy as 'the least of the Great Powers', unable to punch above its weight in the international arena and classed as a 'latecomer' to imperial conquest. In this article, I suggest instead that historians have been looking in the wrong place, and in the wrong period, for evidence of Italian ambition. By concentrating on territorial acquisitions in Africa, they are assessing only a small, relatively unproductive and arguably atypical slice of Italy's global presence. I argue that even before national unification, and long before acquiring a formal Empire, Italy built a global influence structured by the activities of overseas migrants. Yet, despite the recent 'turn' to global history and the stress on diversity in colonial experience, the chronology and geography of the European nation-state still shape our understanding of nineteenth-century Empire. Looking at the hugely successful Italian colony in Peru, at both its commercial and scientific interests and at a violent attempt to establish a settler colony in Chanchamayo, in the Peruvian Amazon, I argue that this Italian world was driven not a nation state but relied instead on a common culture, a culture that was created by a capacity for local assimilation, by Catholic notions of civilisation and by ideas of white racial superiority. Modern imperialism was shaped as much by 'lesser' powers, often before – or without – the nation-state, and in continuity with the practices of the early-modern period. Moreover, mundane migrants could be the most successful empire-builders. I conclude with a call to take note of the full and diverse range of nineteenth-century colonial activities, and not to assume the primacy of formal Empires in the period of 'High Imperialism.'